THE EFFECT OF MORINGA LEAF TEA CONSUMPTION ON BLOOD PRESSURE IN HYPERTENSION SUFFERERS AMONG PROLANIS PARTICIPANTS AT THE SIDABOWA PRIMARY CLINIC, PATIKRAJA DISTRICT, BANYUMAS REGENCY - Pratomo, Anugrah Dimas; Krisnansari, Diah; Laksana, Agung Saprasetya Dwi (Mandala Of Health, 2025)
Hypertension is a condition where blood pressure is higher than normal, and one of its causes is increased inflammation and oxidative stress. Moringa leaves contain high levels of antioxidants, such as flavonoids, which can help control blood pressure as an effort to prevent complications from hypertension. The study aimed to determine the effect of moringa leaf tea consumption on blood pressure in hypertension sufferers among Prolanis participants at the Sidabowa Primary Clinic, Patikraja District, Banyumas Regency. An analytical observational study with a case-control design, which was selected through total sampling. Data analysis was performed using the Independent T Test. The respondents of this study numbered 41 individuals. The results of this study showed the significance values of the blood pressure changes between the two groups: systolic blood pressure 0.146 (p>0.05) and diastolic blood pressure 0.258 (p>0.05), which means there was no effect of moringa leaf tea consumption on blood pressure in hypertension sufferers among Prolanis participants. Consumption of moringa tea did not change the blood pressure of hypertensive patients in prolanis participants of Sidabowa Primary Outpatient Clinic, Patikraja District, Banyumas Regency after consuming moringa tea for 14 days. However, the decrease in systolic blood pressure was greater in the case group.